Hubungan Kadar Gula Darah Dengan Tingkat Depresi Dan Aktifitas Fisik Pada Penderita Diabetes Mellitus - M Faig Mujabi; Wachidah Yuniartika (Jurnal Berita Ilmu Keperawatan, 2018)
High blood sugar levels will cause the occurrence of hyperglycemia. Hyperglycemia occurs because to an impaired insulin secretion or insulin work breakdown. People who hyperglycemia can experience interference in the form of phychological depression and decreased physical activity. People who are depressed and less activity can cause an increase in blood sugar levels. This research is a descriptive study using correlative approach cross sectional aims to do know the relationship between the blood sugar levels with the levels of depression and physical activity in people with Diabetes Mellitus in Sukoharjo Gatak Clinics. Sampling technique using a purpose sampling, while the research instrument using the BDI-II questionnaire of 21 items and IPAQ questionnaire. The result of the calculation of the correlation test product moment relationship with depression level blood sugar levels obtained result and significant value 0.473(p-value) of 0.00. Procut moment correlation test result of the relationship of physical activity with blood sugar levels obtained result –0.460 with a value of 0.00 significance. Then there can be summed up the relationship between the blood sugar levels with the levels of depression and physical activity in people with Diabetes Mellitus in Sukoharjo Gatak Clinics. Where the higher levels of depression, increases blood sugar levels, while the higher physical activity then the lower blood sugar levels.